P75 Teaching emergency oxygen prescribing to medical students. (2nd December 2011) - Earis, J; Deegan, P; Stockton, P; McKinnell, S; Fewtrell, R; Kennedy, T
Abstract : Introduction: In 2008 the BTS published the first National Emergency Oxygen Guidance. Subsequent national audits in 2008 and 2010 have shown poor compliance with these guidelines. In order to improve the use of emergency oxygen Liverpool Medical School has included this topic in a new Patient Safety Programme (PSP) developed to provide practical skills for the 335 fifth year students as a preparation for their Foundation Programme. Methodology: (1)Computer based knowledge test (CBKT) of 60 MCQ questions, based on the BTS guidance and BNF are accessed on-line by the students. Each student has to correctly answer 80% of 10 randomly selected questions. (2) Practical oxygen management session including demonstration of oxygen delivery systems and blood gas sampling in a Clinic Skills Department. (3) Ward based supervised skills including completion of five oxygen prescriptions and blood gas samples. Results: The CBKT score was low with an average of 6.2 of 10 questions answered correctly after the first attempt. After 10 attempts only 72% students passed thus 28% (94 students) were unable to reach the pass threshold. The Abstract P75 table 1 relates the pass rate to the numbers of attempts shows only a modest incremental increase in the cumulative pass rate. In contrast, all students rapidly gained the skills to undertake blood gas sampling and were able to write oxygen prescriptions based on SpO2 results. Conclusions: This study confirms that medical students, like other staff, have a poor basic knowledge about the use of emergency oxygen. The Liverpool PSP is addressing this knowledge gap but in view of the results further education (eg, seminars and e-learning) will be provided prior to the CBKT. We recommend this type of programme to other Medical Schools and clinical staff.